Bureaucratic Challenges in Realizing Sustainable Tourism in Tomohon City - F. Rattu, Stenlie; Mantiri, Jeane; Otnil Toporundeng, Felini (Indonesian Association for Public Administration (IAPA), 2025)
This study aims to identify and analyze the bureaucratic challenges in realizing sustainable tourism in Tomohon City, with four main sub-focuses: inter-agency coordination, government apparatus competence, budget availability, and digitalization. The research method used is a qualitative approach. Data collection techniques include observation, interviews, and literature study. Furthermore, this study applies qualitative data analysis covering data reduction, data presentation, drawing conclusions, and conclusion verification. The findings indicate that several bureaucratic challenges in realizing sustainable tourism in Tomohon City can be seen from four main aspects. First, inter- agency coordination remains weak, as shown by the lack of synchronization between tourism development policies and spatial planning or environmental management. Second, the competence of government apparatus is still inadequate, particularly in understanding sustainable tourism and digital skills, making it difficult for the bureaucracy to adapt to the demands of smart tourism. Third, budget availability is limited and inconsistent, with most allocations directed to major events such as the Tomohon International Flower Festival, while destination maintenance, environmental conservation, and long- term promotion receive less attention. Fourth, digitalization within the bureaucracy has not been implemented optimally due to limited infrastructure, low digital capacity of officials, fragmented systems between agencies, and the digital gap among local tourism stakeholders.